Improving Marketing Performance through Digital Marketing for Micro Business Actors in the Trade Sector Registered at the Cooperatives and SMEs Service Office - Aris Baharuddin; Wahyuni Sulviana Oudina; Yusi Rensi Seppa; Nur Astaman Putra; Ahmad Syarief Iskandar (Universitas Negeri Makassar, 2022)
This study aims to (1) describe and analyze marketing performance through digital marketing for micro business actors in the trade sector at South Sulawesi (2) describe and analyze the dominant factors that affect marketing performance through digital marketing on micro businesses in the trading sector at South Sulawesi. This type of research is descriptive qualitative research with data collection techniques were carried out by interviews, observation, and documentation. Validation of data using credibility, transferability, dependability, and confirmability. Data analysis used is data collection, data condensation, data presentation, and drawing conclusions. The results of the data analysis as well as those that have been described show the three indicators which as a measure in analyzing Marketing Performance Improvement through Digital Marketing show very good results.